2015
DOI: 10.1021/acs.analchem.5b01793
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Detection of Carbon Monoxide in Living Cells by Palladacycle Carbonylation-Based Surface Enhanced Raman Spectroscopy Nanosensors

Abstract: A novel nanosensor was explored for the highly selective detection of intracellular carbon monoxide (CO) by surface enhanced Raman spectroscopy (SERS) on the basis of palladacycle carbonylation. By assembling new synthesized palladacycles (PC) on the surface of gold nanoparticles (AuNPs), SERS nanosensors (AuNP/PC) were prepared with good SERS activity and reactivity with CO. When the AuNP/PC nanosensors were incubated with a CO-containing system, carbonylation of the PC assembled on AuNPs was initiated, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 30 publications
0
66
0
2
Order By: Relevance
“…Using this approach, Dhara and co-workers [28] detected CO in A549 cells incubated with PdCl 2 and CORM-3. Besides these and otherr elated reports, [29,30] Feng and co-workers have prepared CO fluorescent probesb ased on aP d 0 -mediated Tsuji-Trost elimination reaction using 3-benzothiazolyl-7-hydroxycoumarin and fluorescein fluorophores [31a,b] and this has been expanded in more recent work by the same group. [31c,d] Although the probesd escribed above display an impressive ability to detect CO in biological systems, the field would benefit from furtherr esearch to address some of the intrinsic drawbacks of each system,s uch as synthetic complexity (and hence reduced accessibility), delayedf luorescencer esponse times (typically 40-60 mins in Pd-based systems) andt he reduced fluorescencet urn-onr esponse of some of the probes (especially in aqueous solution).…”
Section: Detection Of Co In Cellsmentioning
confidence: 99%
“…Using this approach, Dhara and co-workers [28] detected CO in A549 cells incubated with PdCl 2 and CORM-3. Besides these and otherr elated reports, [29,30] Feng and co-workers have prepared CO fluorescent probesb ased on aP d 0 -mediated Tsuji-Trost elimination reaction using 3-benzothiazolyl-7-hydroxycoumarin and fluorescein fluorophores [31a,b] and this has been expanded in more recent work by the same group. [31c,d] Although the probesd escribed above display an impressive ability to detect CO in biological systems, the field would benefit from furtherr esearch to address some of the intrinsic drawbacks of each system,s uch as synthetic complexity (and hence reduced accessibility), delayedf luorescencer esponse times (typically 40-60 mins in Pd-based systems) andt he reduced fluorescencet urn-onr esponse of some of the probes (especially in aqueous solution).…”
Section: Detection Of Co In Cellsmentioning
confidence: 99%
“…Due to the reduction of azides by H 2 S, structure variations of 4‐AA molecules would cause changes to the SERS spectrum; thus giving rise to successful H 2 S detection. Long and co‐workers developed a CO nanosensor constructed from palladacycle‐assembled AuNPs . They indicated that the corresponding changes to the SERS fingerprint feature could be observed upon the CO‐induced carbonylation of palladacycles.…”
Section: Sers For Intracellular Detectionmentioning
confidence: 99%
“…Long and co-workersd eveloped aC On anosensor constructed from palladacycle-assembled AuNPs. [27] They indicated that the corresponding changes to the SERS fingerprint feature couldb eo bserved upon the CO-induced carbonylation of palladacycles.F urther cellular studies proved that the method could provide efficient detection of CO, with al imit of 0.5 mm.R ecently,L ie tal. presented a SERS-active nanosensor forN Od etection by means of the specific reaction of NO with o-phenylenediamine in the presence of O 2 .…”
Section: Intracellular Gaseous Molecule Detectionmentioning
confidence: 99%
“…a peptide, monoclonal antibody, affibody, or aptamer) which is coupled to the nanoparticle, can be determined by spectrally separating the SERS signatures in the detected signals from a tumor [32]. The SERS technique has excellent selectivity, rapid detection capability, high signal-to-noise ratio, non-photo bleaching features, and the use of single photo-excitation [20]. Another way to obtain larger Raman scattering enhancements, which is in close relationship with SERS, is to put the target molecule in the fractal space between aggregated colloidal nanoparticles, known as ‘hot spots’ [33–36].…”
Section: Principles Of Raman Spectroscopymentioning
confidence: 99%